Altmetric Visibility and ResearchGate Engagement: A Case Study of the University of Jammu - Rehman, Izna; Haridasan, Sudharma (Journal of Information and Knowledge, 2025)
This study presents a case study of the University of Jammu to examine the contributions and visibility of faculty members and research scholars on ResearchGate through altmetric analysis. The study specifically aims to identify the total number of publications by the University of Jammu, identify the top contributing departments, identify the top five contributing authors in terms of publications, citations, h index and research interest score and to examine the relationship between publication, citation, h index and research interest score available on ResearchGate. Data was manually collected from ResearchGate, including name, department, publications, citations, h-index, and research interest score. The researchers found profiles of a total of 301 members on ResearchGate from the University of Jammu. The data was collected in the first week of January 2025. The data was analysed using MS Excel and represented using graphs and Tables. The findings indicate that the department of Physics is the leading contributor across all the metrics, accounting for 41.02% of total publications, 159454 citations and a Research Interest score of 65533.2. Some departments, such as Buddhist Studies, English, and Museology, show minimal presence on ResearchGate, highlighting the need for greater participation of the. The findings will help the university to understand where more participation is needed to improve the contribution of the university to increase the visibility of research on platforms like ResearchGate.